Bilateral Two-Parameter Mock Theta Functions and Related Applications - Wang, Chun (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
In this paper, we investigate new relationships for bilateral series related to two-parameter mock theta functions, which lead to many identities concerning the bilateral mock theta functions. In addition, interesting relations between the classical mock theta functions and the bilateral series are also concluded.